1997
DOI: 10.1136/bmj.314.7078.404
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal risk factors for cerebral palsy in very preterm babies: case-control study

Abstract: Objective: To assess decleration and acceleration in the disease process in the initial phase of epsilepsy in children with new onset tonic-clonic seizures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
118
4
7

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(135 citation statements)
references
References 29 publications
6
118
4
7
Order By: Relevance
“…This process produced 16 article,s which appeared likely to provide information about the relationship between BP and ultrasound brain abnormalities in the neonatal period. 8,13,14,[17][18][19][20][21][22][23][24][25][26][27][28][29][30] These articles are described in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…This process produced 16 article,s which appeared likely to provide information about the relationship between BP and ultrasound brain abnormalities in the neonatal period. 8,13,14,[17][18][19][20][21][22][23][24][25][26][27][28][29][30] These articles are described in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, however, clinicians are commonly faced with critically ill infants who have cardiovascular insufficiency with hypotension, a condition that has also been associated with adverse consequences. [62][63][64][65][66][67] Current therapy for hypotension consists primarily of volume expanders and vasopressors, which only treat the symptom. If the etiology of the hypotension in some of these infants is relative adrenal insufficiency, treatment with hydrocortisone would be more appropriate.…”
Section: Should We Treat Relative Ai In Newborns?mentioning
confidence: 99%
“…More than 50% of extremely low birth weight infants (,1000 g) are treated for clinical or proven neonatal infection during their hospitalization, 12 and the associated mortality is high (20%-40%). [13][14][15] Follow-up studies of preterm infants have suggested an association between inflammation, cerebral white matter damage, and cerebral palsy, [16][17][18][19] but very few studies have directly addressed the possible links between neonatal infections and neurodevelopmental outcomes. 8,20 The objective of the current study was to evaluate the impact of neonatal infections on 5-year neurodevelopmental outcomes in a large population-based cohort of very preterm infants.…”
mentioning
confidence: 99%